2005
DOI: 10.1038/sj.bjc.6602552
|View full text |Cite
|
Sign up to set email alerts
|

A modified Inflammatory Bowel Disease questionnaire and the Vaizey Incontinence questionnaire are simple ways to identify patients with significant gastrointestinal symptoms after pelvic radiotherapy

Abstract: After radiotherapy for pelvic cancer, chronic gastrointestinal problems may affect quality of life (QOL) in 6 -78% of patients. This variation may be due to true differences in outcome in different diseases, and may also represent the inadequacy of the scales used to measure radiotherapy-induced gastrointestinal side effects. The aim of this study was to assess whether outcome measures used for nonmalignant gastrointestinal disease are useful to detect gastrointestinal morbidity after radiotherapy. Results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 24 publications
1
73
0
1
Order By: Relevance
“…We have assessed both (acute and late) measurements prospectively and used a patient-reported symptom tool. Although this tool is not in common use among oncologist or radiographers, we have previously shown that it is more sensitive than commonly used scoring systems in characterizing symptoms associated with both phases (11,12). It incorporates questions that others have found are important but lacking in more commonly used tools (frequency, urgency, and diarrhea) (13) and symptoms that we have found important to patients (anorectal symptoms and excessive flatus) (14), which are ignored by most scoring tools.…”
Section: Discussionmentioning
confidence: 98%
“…We have assessed both (acute and late) measurements prospectively and used a patient-reported symptom tool. Although this tool is not in common use among oncologist or radiographers, we have previously shown that it is more sensitive than commonly used scoring systems in characterizing symptoms associated with both phases (11,12). It incorporates questions that others have found are important but lacking in more commonly used tools (frequency, urgency, and diarrhea) (13) and symptoms that we have found important to patients (anorectal symptoms and excessive flatus) (14), which are ignored by most scoring tools.…”
Section: Discussionmentioning
confidence: 98%
“…Both IBDQ and Vaizey score were selected because of their simplicity and precision, which make those ideal for clinical practice to identify patients who require specialist help and in the clinical research setting to provide a sensitive measure of FI [20,21] .…”
Section: Qolmentioning
confidence: 99%
“…It can imprison clinicians and scientists into ways of thinking which do no service to the patient or to research. For example, it may encourage the erroneous belief that radiation-induced toxicity cannot be improved or prevented and to attempt to do so is futile [21,22], that manipulating the radiation dose will solve all problems, completely ignoring the real nature of normal tissue injury [23][24][25] or that worst of all, it is not terribly important to measure it accurately [25][26][27][28].…”
Section: Imprecise Terminologymentioning
confidence: 99%